(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women must be evaluated at every stage of their lives in order to live a healthy lifestyle free of illnesses like reproductive tract infections (RTI) and sexually transmitted infections (STIs), which may be easily avoided by following excellent reproductive hygiene practises. Because these issues are progressively worsening, it is critical to address them as soon as possible. The purpose of this research was to evaluate the practises of personal, menstrual, and sexual hygiene among married women of reproductive age, to identify early signs of RTIs in them, and to investigate the relationship between important demographic characteristics and RTI symptoms.